2014
DOI: 10.1152/ajpcell.00341.2013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of differentially regulated subsarcolemmal calcium signals activated by vasoactive agonists in rat pulmonary artery smooth muscle cells

Abstract: Subedi KP, Paudel O, Sham JS. Detection of differentially regulated subsarcolemmal calcium signals activated by vasoactive agonists in rat pulmonary artery smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…This "in vivtro" method [Narang et al, 1986] falls somewhere between truly in vitro methods where all the constituents of a system are known, and in vivo methods where the system being assayed is living and consists solely of endogenous components. Similar to Xenopus egg extract systems, it is clear that some cellular activities will be disrupted by establishment of the assay system while other activities, such as nuclear import [Turgay et al, 2010], calcium signaling [Subedi et al, 2014], cardiomyocyte contractility [Altschuld et al, 1985], and platelet function [Lineberger et al, 1989], remain intact. Although PARF may be applicable to the study of a specific subset of cellular processes, the technical capabilities required for PARF are less than those required for other quantitative imaging techniques (such as photoactivation or FRAP), nor does PARF require the technical expertize in protein expression and purification necessary for reconstitution approaches.…”
Section: Parf Is a Flexible And Useful Technique Capable Of Addressinmentioning
confidence: 99%
See 1 more Smart Citation
“…This "in vivtro" method [Narang et al, 1986] falls somewhere between truly in vitro methods where all the constituents of a system are known, and in vivo methods where the system being assayed is living and consists solely of endogenous components. Similar to Xenopus egg extract systems, it is clear that some cellular activities will be disrupted by establishment of the assay system while other activities, such as nuclear import [Turgay et al, 2010], calcium signaling [Subedi et al, 2014], cardiomyocyte contractility [Altschuld et al, 1985], and platelet function [Lineberger et al, 1989], remain intact. Although PARF may be applicable to the study of a specific subset of cellular processes, the technical capabilities required for PARF are less than those required for other quantitative imaging techniques (such as photoactivation or FRAP), nor does PARF require the technical expertize in protein expression and purification necessary for reconstitution approaches.…”
Section: Parf Is a Flexible And Useful Technique Capable Of Addressinmentioning
confidence: 99%
“…Permeabilization has been used to allow manipulation of cytosolic ion concentrations [Altschuld et al, 1985;Smolen et al, 1986], to allow introduction of large macromolecules [Lorenz et al, 2008], and to allow removal of macromolecules [Lineberger et al, 1989]. In many of these experiments, the cell structures that remained following digitonin permeabilization continued to behave similarly to intact cells, allowing researchers to characterize subcellular processes using approaches not available in intact cells or in in vitro reconstitution systems [Marino et al, 2014;Schulz, 1990;Subedi et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, calcium signals are highly dynamic and reliant on a combination of deterministic and stochastic processes. Our laboratory, and others', have previously reported that pulmonary arterial myocytes exhibit whole cell Ca 2ϩ events that are spontaneous or can be activated by various forms of stimulation (34,38,43,46). Although Ca L activation and inhibition affect pulmonary arterial myocyte contractions by modifying intracellular Ca 2ϩ events, the coupling between cell activation, Ca 2ϩ responses, and the resulting myocyte contractions is not completely understood (46).…”
Section: Introductionmentioning
confidence: 98%
“…Their divalent character makes them strong binders; hence, their physiological concentration must be strictly controlled. The concentration of Ca 2+ in the extracellular space is about 2 mM, while its intracellular levels are much lower and range amongst cell organelles from 100 nM in the cytosol to 600 μM in the endoplasmic reticulum12. The maintenance of low intracellular calcium concentrations is achieved, among other mechanisms, by calcium buffers which include both cytoplasmic and membrane-anchored calcium-binding proteins134.…”
mentioning
confidence: 99%